2001
DOI: 10.1002/job.86
|View full text |Cite
|
Sign up to set email alerts
|

Team mental models in a team knowledge framework: expanding theory and measurement across disciplinary boundaries

Abstract: SummaryBecause research on team mental models is still in its formative stages, there is a need for continued conceptual development of the construct and direct empirical support linking team mental models to team outcomes. Researchers in other ®elds have developed concepts that are distinct from, but clearly related to team mental models, including information sharing, transactive memory, group learning, and cognitive consensus. Although these research streams currently exist in parallel with little cross-fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
480
0
11

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 663 publications
(510 citation statements)
references
References 43 publications
6
480
0
11
Order By: Relevance
“…Empirical work, however, has lagged behind conceptual development (Mohammed & Dumville, 2001). Some early research used team mental models as a post hoc explanation for observed performance differences among teams, although more recent research has measured the construct more directly.…”
Section: See March 2001 Issue Of Journal Of Organizational Behaviormentioning
confidence: 99%
See 2 more Smart Citations
“…Empirical work, however, has lagged behind conceptual development (Mohammed & Dumville, 2001). Some early research used team mental models as a post hoc explanation for observed performance differences among teams, although more recent research has measured the construct more directly.…”
Section: See March 2001 Issue Of Journal Of Organizational Behaviormentioning
confidence: 99%
“…The application of the concept to work teams involves a similar logic. Each team member keeps current on who knows what, channels incoming information to the appropriate person, and has a strategy for accessing the information (Mohammed & Dumville, 2001). In addition to knowing who is the expert in different knowledge areas, transactive memory also involves storing new information with individuals who have matching expertise and accessing relevant material from others in the system (Wegner 1986(Wegner , 1995.…”
Section: See March 2001 Issue Of Journal Of Organizational Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…Shared mental models can refer to shared representations of tasks, equipment, working relationships and situations (Mohammed and Dumville 2001). It is stated that probably all of these types of knowledge need to be shared in effective teams.…”
Section: Shared Mental Modelsmentioning
confidence: 99%
“…Psychological framing effects are theoretically amplified by the automatic spreading activation of memory from one construct to another with which it is semantically related (for example, activation of "special rights" may heighten the odds that ideas such as "inequity," "privilege," or "affirmative action" will also be stimulated). In the group context, the relevant knowledge store is a collective fund of ideas held by assembled group members-what psychologists have termed a "transactive memory system" (Hollingshead 1998;Wegner 1995)-and the spreading activation of constructs across the group takes place not only psychologically but also interpersonally, through discussion (see also recent research in organizational behavior on "shared cognition" and "team mental models"-e.g., Cannon-Bowers and Salas 2001; Mohammed and Dumville 2001). The ideological makeup of the groups should profoundly affect the availability of constructs in the transactive memory system, such that conservative groups will tend toward more negatively loaded constructs, while liberal groups possess shared ideas that, if not positively valenced, will at least be less negatively inclined toward gay civil unions.…”
Section: Research Questions and Hypothesesmentioning
confidence: 99%